Implementation of Discovery Learning Model on the Learning Motivation of Sixth Grade Students - Kurniawati, Ani (Universitas Pendidikan Indonesia, 2023)
The research objective was to determine the effect of the discovery learning model on the student learning motivation. This study employed the classroom action research method. The research population were MI PUI Cigadog students, involving sixth-grade students (30 students) as samples. The sampling technique used was the total sampling. The instruments utilized were observations and questionnaires. The results of the first cycle of learning showed an achievement of 65.04%, as derived from data tabulation, falling into the category of satisfactory. Meanwhile, in the second cycle, through the evaluation and the successful refinement of the implementation of the discovery learning model, a significant improvement was observed. The percentage of learning motivation questionnaire results in the second cycle was 73.47%. The learning motivation outcomes fell into the